SISTEM INFORMASI MANAJEMEN KLINIK PADA KLINIK PRATAMA “RUMAH SEHAT” - Iis Istiqomah; Okta Irawati (CV. Multi Kreasi Media, 2023)
The data management system of clinical data that is still done manually, requires a long time and not accurate so that sometimes there are some income or expenses that have not yet been recorded. In addition to the data management of clinical data, data search also still done manually. Data search patients and medical records of patients who had treatment before need a long time because the amount of data of patients who registered and the accumulation of medical record data enough. The other problem is not the media that cover on the information from the Klinik Pratama